2018
DOI: 10.1037/ocp0000073
|View full text |Cite
|
Sign up to set email alerts
|

Daily spillover from family to work: A test of the work–home resources model.

Abstract: The present study examines a mediated moderation model of the day-level effects of family hassles and family-work spillover (affect and cognition) on the relationship between job resources and employees' flourishing at work. Based on the work-home resources model, the authors hypothesized that demands from one domain (family) induce repetitive thoughts or negative feelings about those problems, so that individuals are not able to function optimally and to make full use of contextual resources in the other doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 72 publications
4
67
0
Order By: Relevance
“…This contributes to recent research on the consequences of FSSBs (e.g., Las Heras, Rofcanin, Bal, & Stollberger, 2017;Rofcanin, Las Heras, & Bakker, 2017;Russo, Buonocore, Carmeli et al, 2015) and theory on work-family enrichment (Weer, Greenhaus, & Linnehan, 2010), which has tended to overlook the issue of whether and how FSSBs may conflict with focal employees' family and work domains. From a W-HR model perspective, we expand this model by integrating and exploring mechanisms (i.e., family performance) and contextual conditions (i.e., prosocial motivation) under which resources gained in work domain (i.e., FSSBs) may spillover to home domain (family domain) which are then expected to drive better functioning at work (Du et al, 2017;Ten Brummelhuis & Bakker, 2012).…”
Section: On Page 16 Some Covariates Do Correlate With the Major Varimentioning
confidence: 99%
See 1 more Smart Citation
“…This contributes to recent research on the consequences of FSSBs (e.g., Las Heras, Rofcanin, Bal, & Stollberger, 2017;Rofcanin, Las Heras, & Bakker, 2017;Russo, Buonocore, Carmeli et al, 2015) and theory on work-family enrichment (Weer, Greenhaus, & Linnehan, 2010), which has tended to overlook the issue of whether and how FSSBs may conflict with focal employees' family and work domains. From a W-HR model perspective, we expand this model by integrating and exploring mechanisms (i.e., family performance) and contextual conditions (i.e., prosocial motivation) under which resources gained in work domain (i.e., FSSBs) may spillover to home domain (family domain) which are then expected to drive better functioning at work (Du et al, 2017;Ten Brummelhuis & Bakker, 2012).…”
Section: On Page 16 Some Covariates Do Correlate With the Major Varimentioning
confidence: 99%
“…"The findings of this study also contribute to and extend the WH-R model in a number of ways. Drawing on the W-HR model, a recent study by Du et al (2017) revealed that homesickness, conceptualized as contextual resource, attenuates the positive association between job resources (feedback and social support) and work performance (task and contextual performance). The authors argue that homesickness depletes from a focal employee's time, energy and other personal resources, hence diminishing work performance.…”
mentioning
confidence: 99%
“…In discussing the results in this study, we adopted the spillover theory, which focuses on the relationships (attitudinal, behavioural and experiential) connecting family to work (and vice versa) [see Staines, 1980]. In view of recent research by Du, Derks, and Bakker (2018) showing that negative emotions stemming from domestic hassles could transfer or “spill over” to the workplace and hamper work productivity, we proposed that family‐related stressors could trigger deviant work behaviours in nurses, which usually co‐occur with nurses’ lower work productivity. In other words, we hypothesized that:
Hypothesis 1: Negative emotions could mediate the relationship linking social undermining in families to deviant work behaviours (see Figure 1).
…”
Section: Introductionmentioning
confidence: 99%
“…This might reflect the taxing effects of “emotional labor” (labor requiring consistent, seemingly cheerful attention to others’ needs), which is shouldered disproportionately by women in both workplace and family spheres (Guy and Newman, 2004; Du et al, 2018). …”
Section: Discussionmentioning
confidence: 99%